Psychometric Properties of the Preschool Age Psychiatric Assessment (PAPA) in Farsi: Based on DSM-5 - shahriari, farshid; Norouzi, Sanaz; Malek, Ayyoub; Amiri, Shahrokh; Sadeghi Bazargani, Homayoun; Hassanzadeh, Mohammadbagher; Egger, Helen Link; Small, Brian (Iranian Journal of Child Neurology, 2023)
Objectives The first onset of many psychiatric disorders usually occurs inchildhood or adolescence. The structured interview of Preschool Age Psychiatric Assessment (PAPA) was developed in response to the need for a standardized and reliable method to assess psychiatric disorders in preschool-age children. This study aimed to translate DSM-5-based PAPA into Farsi and evaluate its face and content validity and reliability. Materials & Methods The procedure was a forward translation of PAPA to Farsi, evaluation for face and content validity, finalization of items within the expert panel, backward translation to English, matching the original PAPA with randomly selected items from the backward translation version, and revision as needed, and finally evaluation for the validity of the changes for localization and cultural considerations. The interviews based on the final Farsi version were performed on thirty parents of children from two to five years old (chosen from Tabriz health centers) to determine the reliability and were repeated at an interval of two weeks. Results The mean of CVI=0.91 and Modified Kappa=0.90 were obtained, and reliability with Cronbach’s alpha was 0.89. Conclusion The Farsi version of the DSM-5-based PAPA diagnostic interview has good face and content validity and reliability.